Screening of antioxidant and anti-inflammatory activities among thiopyrano[2,3-d]thiazoles - Lozynskyi, A.V.; Kaminskyy, D.V.; Romanchyshyn, Kh.B.; Semenciv, N.G.; Ogurtsov, V.V.; Nektegayev, I.O.; Lesyk, R.B. (Вiopolymers and Cell, 2015)
The aim of present research was the investigation of antioxidant and antiexudative activities of the series of thiopyrano[2,3-d]thiazoles synthesized based on cinnamic acid amides. Methods. Organic synthesis; spectral methods; free radical scavenging assay (DPPH test); evaluation of antiexudative activity (carrageenan oedema model in rats). Results. The evaluation of the free radicals scavenging activity and antiexudative activity of series of the 2-oxo-5-phenyl-7-aryl(hetaryl)-3,7-dihydro-2H-thiopyrano[2,3-d]thiazole-6-carboxylic acid amides was performed. Among the tested compounds, rel-(5R,6S,7S)-N-(4-methylphenyl)-7-(4-methylphenyl)-2-oxo-5-phenyl-3,5,6,7-tetrahydro-2H-thiopyrano[2,3-d]thiazole-6-carboxamide possessed the highest level of both activities. The experimental data most probably indicate a pronounced effect of methyl groups (phenyl fragments) on the realization of the anti-inflammatory and antioxidant effects and allow a suggestion about the antiradical mechanism of anti-inflammatory activity of the target compounds. Conclusions. The anti-inflammatory and free radicals scavenging activities of some tiopyrano[2,3-d]thiazoles have been established and the most active compounds were identified. Some findings of the structure-activity relationship were set up.